Description and molecular characterization of Longidorus orientalis (Loof, 1982) associated with date palm (Phoenix dactylifera L.) in Iraq - Ali Z. Abed; Baida G. Ofi; Muhanned Al-W Waeli; Mohammed H. Abass (Universitas Lampung, 2026)
Soil samples from the rhizosphere of date palm (Phoenix dactylifera L.) trees were collected from orchards in Basrah Province, southern Iraq, a major region for date palm cultivation. This study aimed to isolate and identify plant-parasitic nematodes associated with date palms. Samples were collected from the root zone surrounding the trees, and nematodes were extracted using a sieving technique. Morphometric measurements were obtained from nematodes mounted on permanent slides. To confirm species identification, DNA was extracted from individual females, and the D2–D3 region of the 28S rRNA gene was amplified using PCR. Morphometric and molecular analyses confirmed the species Longidorus orientalis. Sequencing of the D2–D3 region (553 bp) showed 100% similarity with an Iranian isolate (GenBank accession no. GQ988722.1). The nucleotide sequence of the Iraqi isolate was deposited in GenBank under accession no. PV416847.1. This study represents the first record of L. orientalis associated with date palms in Iraq, highlighting its potential as a pathogenic threat and emphasizing the need for sustainable management strategies to reduce its impact and prevent further spread.